2004
DOI: 10.1016/j.ejvs.2003.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Is a Type II Endoleak after EVAR a Harbinger of Risk? Causes and Outcome of Open Conversion and Aneurysm Rupture during Follow-up

Abstract: Endoleak type II may not be harmless as it was more frequently associated with enlargement of the aneurysm and reinterventions. Large aneurysms and migration of the device were the main risk factors for rupture. The clinical implications of these findings may involve more frequent surveillance visits for patients with type II endoleak. Aneurysm expansion is a clear indication for reintervention. Patients with large aneurysms, 65 mm or larger, may also benefit from a more comprehensive surveillance schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
187
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(205 citation statements)
references
References 40 publications
(36 reference statements)
12
187
4
2
Order By: Relevance
“…This study end point has been used in other published reports, 20,21 and has been associated with an increased risk of adverse outcomes, including the need for subsequent open repair and aneurysm rupture. 22,23 The natural history of untreated aneurysms is to enlarge over time until eventual rupture. Endovascular repair aims to prevent aortic rupture; thus, AAA sac enlargement represents treatment failure, because it leaves the patient at risk of death resulting from rupture.…”
Section: Discussionmentioning
confidence: 99%
“…This study end point has been used in other published reports, 20,21 and has been associated with an increased risk of adverse outcomes, including the need for subsequent open repair and aneurysm rupture. 22,23 The natural history of untreated aneurysms is to enlarge over time until eventual rupture. Endovascular repair aims to prevent aortic rupture; thus, AAA sac enlargement represents treatment failure, because it leaves the patient at risk of death resulting from rupture.…”
Section: Discussionmentioning
confidence: 99%
“…3) Persistent type II endoleak has been associated with a higher incidence of adverse outcomes, including aneurysmal sac growth, need for reintervention and for conversion to open repair, and rupture. 4,5) The most commonly involved branches are the inferior mesenteric artery (IMA) and lumbar arteries (LA), which are usually covered with endografts. Various strategies have been advocated for managing persistent type II endoleak with some investigators recommending preemptive adjunctive procedures such as IMA coil embolization to preclude type II endoleak.…”
Section: Introductionmentioning
confidence: 99%
“…Marrewijk et al similarly claimed that T2Ls are not benign, and suggested that aneurysm expansion >8 mm is an indication for reintervention [17]. A retrospective analysis of 700 patients undergoing EVAR also demonstrated how T2Ls may not always have a benign course [18].…”
Section: Journal Of Vascular and Endovascular Surgery Issn 2573-4482mentioning
confidence: 97%